(3cJGH aj GdCOHs - (3MeOhf Hf YHO GdQMef Hf MeOhf GdSdej GdeQOGSj, CHh GdajV, GdeYQha HGHf GdMGL,J (B1232 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHhGdaVd SjOj CMeO HYV GdcdGe aj GdCOH JhWCI deG CQOfGg ef TQM cJGH ehdGfG CjOg Gddg ceG SjPcQ(B: (3MeOkG def eqdc edhc GdYOd s
(3BNQgG (B:s
(3hJhLg HJGL YfGjJc aj SqQg hfLhGg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B228 - (3U(B309s
(3HgG fXGe GdJYbjHIs
(3cGf GdeDda MjkG (B1269(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B76s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B136 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs